Avaliaç\~ao dos impactos econômicos do fundo costitucional de financiamento do Centro-Oeste (FCO) entre 2004 e 2010 - Guilherme Mendes Resende; Tulio Antônio Cravo; Murilo José de Souza Pires (Instituto de Pesquisa Econômica Aplicada (IPEA), 2014)
– The paper aims to evaluate the economic impact of the Center-West Constitutional Regional Fund (FCO). The study uses different spatial scales to analyse the impact of FCO on GDP per capita growth between 2004 and 2010. The results of the fixed effects panel data estimations show that FCO impacts positively GDP per capita growth only at municipal level and results suggest that this positive effect are mainly influenced by the specific FCO line of credit empresarial . The results for micro and mesorregions suggest that FCO does not stimulate economic growth in more aggregated regions.
Keywords: C52; R58; 330; impact evaluation; regional development; FCO; Center-West; Brazil